Record of Thaumantis diores and Gerosis sinica Butterflies from Bangladesh - Hossain, Md Monwar; Habib, Mirza Shamim Ahasan; Islam, Md Shahtabul; Akter, Farjana; Khan, Sabbir Hussain; Sultana, Selina; Rima, Nourin (Bangladesh Journal of Zoology, 2016)
Abstract not available Bangladesh J. Zool. 43(2): 321-326, 2015